Pengaruh Harga, Kualitas Produk, Inovasi Produk Dan Gaya Hidup Terhadap Keputusan Pembelian Melalui Brand Image Sebagai Variabel Intervening - Dede Syafulloh; Suwignyo Widagdo; Saiful Amin (Program Studi Manajemen, Sekolah Tinggi Ilmu Ekonomi Mandala, 2022)
This study aims to determine the effect of price, product quality, product innovation and lifestyle on purchasing decisions and their effect on brand image as an intervening variable at Rumah Batik Rolla Jember. The population in this study are consumers from Rumah Batik Rolla Jember. The sample used as many as 60 respondents who are consumers of the House of Batik Rolla Jember. The sampling technique used is purposive sampling. The data analysis method used is path analysis with the help of SPSS 23. The results show that price and product innovation have no direct effect on brand image, while product quality and lifestyle have a direct effect on brand image. In addition, price, product quality, product innovation, lifestyle and brand image have a direct influence on purchasing decisions. Price and product innovation have no indirect effect on purchasing decisions through brand image, while product quality and lifestyle have an indirect effect on purchasing decisions through brand image.